Efficacy of Brucella abortus S19 and RB51 vaccine strains: a systematic review and meta-analysis - Oliveira, Marina Martins de (2022)
Bovine brucellosis is a zoonosis that affects the whole world, most often in developing countries, and vaccination with the S19 or RB51 vaccines is the main way to prevent the disease. This study aimed to review the literature that estimated the effectiveness of both of the most used vaccines against bovine brucellosis in order to gather the main information from experimental studies, such as dose, route of administration, challenge dose, among others, in addition to recalculating the effectiveness of the two main vaccines for cattle. The most used vaccine strain was S19, at a dose of 1010 colony forming units (CFU), followed by the RB51 vaccine strain at 1010 CFU. The most used challenge strain was Brucella abortus 2308, at a dose of 107 CFU by intraconjunctival route. For the recalculation of vaccine efficacy, a meta-analysis was performed, in which the main results were that the S19 vaccine at a dose of 109 CFU presented greater protection against infection and abortion than the other vaccine doses, while the RB51 vaccine at a dose of 1010 UFC exhibited greater protection against both clinical signs and infection than the other dose of the same vaccine. It was possible to conclude that the S19 vaccine at a dose of 109 CFU and the RB51 vaccine at a dose of 1010 CFU administered subcutaneously were the most effective to prevent abortion and infection against the experimental challenge with Brucella abortus 2308 at a dose of 107 CFU by intraconjunctival route.